Prevalence of Toxoplasma gondii infection among animals in Algeria: A systematic review and meta-analysis. (February 2021) - Ouchetati, Imane; Ouchene-Khelifi, Nadjet Amina; Ouchene, Nassim; Khelifi, Manal; Dahmani, Ali; Haïf, Asma; Zeroual, Fayçal; Benakhla, Ahmed
Highlights: Toxoplasma gondii is a worldwide zoonotic parasite that can infect all warm-blooded animals and humans of which felids are definitive hosts. Current findings on the prevalence and risk factors associated with T. gondii infection in animal species in Algeria were reviewed in this study according to the recommendations of the PRISMA guideline. A total of 14 papers from 1955 to 2020 were eligible to be included in this systematic review and meta-analysis study including a number of 10, 187 animals of which 25.46 % were positive cases. Prevalence of Toxoplasma-infection was 70.31 % in stray cats, 50.70 % in poultry farms, 33.61 % in goats, 30.47 % in dogs, 30 % in donkeys, 28.17 % in horses, 22.57 % in sheep, 20.04 % in cattle and 14.57 % in local rabbits. The most important factors that influenced this prevalence were age, sex and animal species. Adult animals and females, stray cats and poultry were the most infected. Rabbits were the least infected. Abstract: Toxoplasma gondii is a zoonotic parasite that can infect all warm-blooded animals. It is responsible for considerable economic losses in some regions and farming systems. This review aims to synthesize current findings on the prevalence and risk factors associated with T. gondii infection in animal species in Algeria. It was performed according to the recommendations of the PRISMA guideline. A total of 14 papers from 1955 to 2020 were eligible to be included in this systematic review and meta-analysis study including a number of 10, 187 animals of which 2594 were positive cases (25.46 %) (24.62–26.31 %, 95 %CI). Prevalence of Toxoplasma -infection was 20.04 % in cattle, 22.57 % in sheep, 33.61 % in goats, 28.17 % in horses, 30 % in donkeys, 70.31 % in stray cats, 14.57 % in local rabbits, 30.47 % in dogs and 50.70 % in poultry farms. Adult animals and females were most infected. The highest prevalences were reported in stray cats and poultry. Rabbits were the least infected. This analysis showed a trend of increasing infection since 2015 (R² = 0.129, p > 0.05) which requires further studies to provide better prevention strategies.